ANTIBIOTICS RESISTANCE PROFILE OF ESCHERICHIA COLI AND ENTEROBACTER AEROGENES ISOLATED FROM WELL WATERS IN AGO-IWOYE, SOUTHWESTERN NIGERIA - Bello, Temitope Kudirat; Olorunjuwon O., Bello; H.O., Egberongbe; Ikimot A., Azeez; Afolabi, Oluwadun (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
Eighty percent of all diseases are attributed to unsafe water with about 11.4 billion people in the world suffering from major related diseases at various times. This study was carried out to investigate the antibiotics resistance profile of Escherichia coli and Enterobacter aerogenes isolated from well waters in Ago-Iwoye, Southwestern Nigeria. Water samples were collected from ten different wells. The multiple tube fermentation technique was employed to enumerate coliforms using MacConkey broth. Nutrient agar and ethylene methylene blue (EMB) agar were used for the enumeration of Escherichia coli and Enterobacter aerogenes. Biochemical characterization was carried out using standard methods. The disk diffusion method was used to determine the antibiotics susceptibility profiles of the bacterial isolates. Results showed that wells contained most probable number (MPN) of bacteria ranging from 43 to 1,100 bacteria per 100 ml. E. coli was present in eight of the wells while E. aerogenes was present in all the wells. Wells B and C had the highest incidence of E. coli with 5.0 x 102 CFU/100ml while wells D and J had no incidence of E. coli. Occurrence of Enterobacter aerogenes was highest in well B (4.5 x102 CFU/100ml), followed by well C (4.0 x102 CFU/100ml) while the lowest occurrence was obtained from well F having a count of 2.0 x 102 CFU/100ml. E. coli was resitant to nitrofurantoin, ampicillin, cephalocidine, sulphafurazole, carbenicillin and sulfamethazole while E. aerogenes was sensitive to colistin, gentamicin and nitrofurantoin but resistant to the remaining antibiotics of the Gram negative disc. For the U4 disc, E. coli was susceptible to colistin sulphate and resistant to all other antibiotics. E. aerogenes was resistant to the entire U4 discs. The presence of E. coli and E. aerogenes suggested faecal pollution, hence the quality of the wells fell strongly below the standard of safe drinking water. Most strains of isolates showed relative resistance to antibiotics investigated in this study and this should be of great concerns to researchers.